Natural sciences in early childhood: Teaching magnetism to preschool children using Information and Communication Technology - Skothou, Stavroula; Trapali, Maria (European Scientific Journal, ESJ, 2025)
The aim of this publication is to report and approach the field of science in preschool age. More specifically, through the field of natural sciences, the approach of the concept of magnetism, the properties and types of magnets was chosen based on the interest of children. The realization of the educational process started with a set of planned activities undertaken by the educator and then the use of communication and information technologies was integrated, with a series of educational software and tools used by the children. The creation of an improvised story, a fairy tale scenario was the springboard for the realization of the respective activities and then through the use of Information and Communication Technology (ICT), an attempt is made to verify the aforementioned knowledge about magnetism and magnets. The use of the above technological tools and software is a decisive factor both for the repetition of the knowledge already acquired and for the use of new technological tools that will provide a challenge for the development of the pedagogical process.